Amorphous phase of SnO₂ doped Al₂O₃ thin film: optical and structural properties / Puteri Sarah Mohamad Saad … [et al.] - Mohamad Saad, Puteri Sarah; Mohd Zani, Muhammad Nizar Aiman; Aziz, Anees; Hashim, Hashimah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
Tin Oxide (SnO2) is an n-type semiconductor with a direct bandgap of 3.6eV. It is highly conductive, transparent, and gas sensitive. The SnO2 can be unstable depending on certain parameters and methods to prepare it. In this work, the thin film of SnO2 doped with Al2O3 was deposited by electrospinning on glass substrates. The thin films were then annealed at 100°C, 200°C, 300°C, 400°C, 500°C, and then the optical and physical films were examined. Measurements of X-Ray Diffraction (XRD) and Microscope were performed for structural and morphological analysis. The optical characteristics were analyzed using the UV-Vis spectrophotometer. As the annealing temperature increases, the optical transmittance also increases due to the increase in film homogeneity and the degree of crystallinity of the film. The rise in temperature leads to a decrease in absorption values.